Barriers in Inclusive Mathematics Learning for Students with Special Educational Needs - Tia Agnesa; Laura Tisya Yordani; Khairunnisa Eka Permata Sari; Dela Devita; Yunita Widia Putri (Tunjuk Ajar: Journal of Education and Culture, 2025)
Inclusive mathematics education aims to ensure that students with special educational needs (SEN) have equal learning opportunities alongside their peers. However, its implementation still faces multidimensional barriers, including limited teacher competence, rigid curriculum, low student motivation and self-concept, restricted use of assistive technology, communication challenges, classroom management difficulties, and the absence of shadow teachers. This study seeks to identify these barriers while offering a conceptual framework mapping the relationships between barriers and potential solutions. The methodology employed is a PRISMA-guided systematic literature review (SLR), analyzing 12 selected articles from an initial pool of 147 obtained from Scopus, Google Scholar, and DOAJ (2021-2025). Findings reveal that these barriers are interrelated, reinforcing one another and exacerbating learning difficulties. The novelty of this study lies in the development of a barrier-solution conceptual framework and the application of a more transparent review method with critical appraisal. Policy and practice implications highlight the urgency of continuous inclusive teacher training, adaptive curriculum design based on Universal Design for Learning, integration of assistive technology, provision of shadow teachers, and affective strategies to strengthen SEN students’ confidence. These findings provide a foundation for future interventions and inclusive education policies in Indonesia and beyond.